Social protection in South Africa: a quest for an appropriate dispensation through a Minimum Employment Guarantee Scheme - Skosana, Nkere Gerald (University of Cape Town, 2017)
This study has analysed the unemployment phenomenon globally and in particular to the South African situation and contends that a solution to the reduction of the intractable unemployment levels lies in the implementation of a Minimum Employment Guarantee Scheme. It has further analysed the South African social protection system, and highlighted the gaps that currently exist in terms of providing social security, to the multitudes of the unemployed and poor. This is in spite of the constitution guaranteeing the right to social security and social assistance to those who are unable to look after themselves. The study further notes the limitations imposed on government in spite of constitutional provision that guarantees access to social security by the clause that limits this right to the ability of the state to provide this right within its means. Central to the exclusion of these multitudes of the unemployed is a cohort of people between the ages of 19-35 who in terms of the policies of the country are regarded as the youth. Statistics have been shown of the magnitude of this problem amongst young people between the ages of 19-24 and the risks associated with this problem have been highlighted. The study has argued that the existing Public Employment Programmes are not as effective as they should be because there is no mechanism to enforce policy decisions and as such, while there may be a range of programmes meant for youth upliftment as highlighted, these are also not going to be effective unless and until like the Indian model, the issue of employment creation for the youth becomes a subject of statute. The EPWP Social Sector is proposed as a viable model to test such a statute based on its design features and the nature of activities undertaken in the sector are less of a technical nature and require neither sophisticated training nor equipment. Most of these challenges addressed in the sector happen in the communities and recruitment and selection could easily be done amongst the throngs of youth that reside in those communities. As a matter of fact almost half of the participants within the programme currently are youth. It is in the best interest of the country, the study contends, that a dispensation be set up to cater for the lot of the unemployed youth and in this case a Minimum Employment Guarantee Scheme is proposed based on existing models of PEPs in the country.